DISSOLUTION OF CORUNDUM AND ANDALUSITE IN H2O-SATURATED HAPLOGRANITIC MELTS AT 800°C AND 200 MPA: CONSTRAINTS ON DIFFUSIVITIES AND THE GENERATION OF PERALUMINOUS MELTS - Acosta-vigil A.; London D.; Dewers T.A.; Morgan G.B. (My University, 2002)
The mechanisms and kinetics of equilibration between peraluminous minerals and granitic melt were investigated experimentally by the dissolution of corundum and andalusite into H2O-saturated metaluminous haplogranitic melt at 800°C and 200 MPa. Mineral and haplogranitic glass rods were juxtaposed inside platinum capsules, and then subjected to experimental conditions for times ranging from 12 to 2900 h. Upon melting, the mineral –melt interface retreats with the square root of time. The composition of the melt at the interface changes with time, but its ASI [aluminum saturation index = molar Al2O3/(CaO + Na2O + K2O)] remains constant at ?1·20 after 480 h. This value is close to the ASI of an H2O-saturated haplogranitic melt in equilibrium with corundum or andalusite, which may indicate that the composition of the melt at the interface follows the liquidus of these minerals in the system. Sodium and potassium diffuse rapidly uphill across the entire length of the charge towards the interface, resulting in a rapid and uniform increase in ASI throughout the entire melt column. This uphill diffusion of alkalis is due to coupling with excess aluminum entering the melt at the interface, and involves long-range communication in the melt via chemical potential gradients. The evolution of oxide concentration profiles with time suggests that sodium, potassium, and a combination of aluminum and alkalis constitute three directions in composition space along which diffusion is uncoupled (eigenvectors) this system. The aluminum–alkali eigenvector has a molar Al/(Na + K) ratio of ?1·20; its Na/K ratio, however, changes with the composition of the liquid and with time as the entire melt column approaches equilibrium. The solubility of H2O shows a positive correlation with the excess aluminum content of melt, but conclusions about the stoichiometry of H2O in the aluminum– alkali eigenvector could not be obtained from our results. We propose that some H2O may provide charge balance for excess aluminum. Multicomponent diffusion models yield eigenvalues for the corresponding aluminum–alkali eigenvector of 0·3 ? 10?10 to 1·9 ? 10?10 cm2/s. Calculated effective binary diffusion coefficients for Al2O3 are higher, 1·0 ? 10?9 to 3·6 ? 10?9 cm2/s. These diffusion coefficients are used to calculate equilibration times between peraluminous minerals and granitic melts in a model system in which two grains of corundum or andalusite 1 cm apart are connected via a narrow melt column. At the conditions of the experiments, diffusive equilibrium through initially metaluminous H2O-saturated melt would be attained within ?101–102 years. At H2O activity well below saturation of the melt, lower diffusivity of all components may increase the time to equilibration to ?104–105 years, approaching possible time frames for the generation and extraction of crustal melts.